An intervalence complex on chitosan surface and its application for isoniazid detection in synthetic samples - Pereira Barbosa, Priscila Fernanda [UNESP]; Albuquerque Andrade, Rômulo Davi; Vieira, Eduardo Guimarães; Ribeiro do Carmo, Devaney [UNESP] (Elsevier, 2020)
In the current article it is described the preparation of a natural polymeric material formed by chitosan and a complex (copper hexacyanoferrate II) for application as voltammetric sensor for isoniazid (ISO) using a carbon paste electrode (GPE). The material (CuFeCHT) was characterized by scanning electron microscopy (SEM), infrared spectroscopy (FT-IR), X-Ray diffraction (XDR) and Energy Dispersion Spectroscopy (EDS). The CuFeCHT voltammetric behavior was achieved using a GPE which showed two redox couples with formal potential (Eθ’) of 0,30 and 0,73 for each process, attributed to Cu+/Cu2+ and Fe2+(CN)6/Fe3+(CN)6 processes, respectively (KCl; 1.00 mol L−1; ν = 20 mV s−1; 40% (w/w)). ISO determination was carried out employing cyclic voltammetry (CV) and square wave voltammetry (SWV). For SWV method a detection limit (3σ) of 2.47 × 10−5 mol L−1 with relative standard deviation of 0,7% (n = 3) and amperometric sensitivity of 7.13 × 10−3 A mol L−1 was achieved. The effect of concomitant species on the voltammetric response was investigated using both techniques and the proposed methodology was applied for ISO determination using synthetic human urine samples spiked with ISO. Recovery values varied from between 98.28 and 105.14% for CV and between 95.29% and 100.93%.
Keywords: Chitosan; Copper hexacyanoferrate; Cyclic voltammetry; Square wave isoniazid